(untitled) (Indonesian Journal of Agricultural Resource and Environmental Economics, 2025)
Seasonal changes affect capture fisheries activities, as experienced by fishers in Jatimalang Village, Purworejo Regency. These changes have led to a decrease in catches and increased uncertainty in fishermen’s income. This study aims to (1) examine fishers’ perceptions of the impacts of seasonal changes in Jatimalang Village, and (2) estimate changes in fisher households’ income due to seasonal variations. This study used a case study method. The data analysis methods include quantitative descriptive analysis using a Likert scale and analysis of fishermen’s income. The results indicate that fishers acknowledged the impact of seasonal changes in Jatimalang Village, with an average score of 3,09 on a 4,00 scale. Fishermen’s income decreased by 51,71% or IDR 1.728.197 per month during the harvest season, and decreased by 69,18% or IDR 1.097.819 per month during the lean season. Perubahan musim memberikan dampak terhadap kegiatan perikanan tangkap, yang dirasakan oleh nelayan di Desa Jatimalang, Kabupaten Purworejo. Perubahan ini diduga mengakibatkan penurunan hasil tangkapan dan ketidakpastian pendapatan nelayan. Penelitian ini bertujuan untuk (1) mengkaji persepsi nelayan mengenai dampak perubahan musim di Desa Jatimalang, dan (2) mengestimasi perubahan pendapatan keluarga nelayan akibat perubahan musim. Metode penelitian menggunakan metode studi kasus. Metode analisis data yang digunakan yaitu metode deskriptif kuantitatif dengan skala Likert dan analisis pendapatan nelayan. Berdasarkan hasil penelitian, nelayan menyatakan setuju merasakan dampak perubahan musim di Desa Jatimalang, dengan rataan skor sebesar 3,09 dari skala 4,00. Pendapatan nelayan menurun 51,71% atau Rp1.728.197/bulan pada musim panen, serta menurun sebesar 69,18% atau Rp1.097.819/bulan pada musim paceklik.